KOMBINASI TABLET FE DAN KURKUMIN TERHADAP GEJALA DISMINORHE PADA REMAJA PUTRI ANEMIA - admin ilkes (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2017)
The problem of nutrition in adolescents who need special attention is anemia. Adolescents are among those who are prone to anemia due to monthly menstruation and growth. The objective of this study was to investigate the effect of curcumin on menstrual symptoms in adolescent girls anemia. Experimental research design. The sample size of 66 people was selected proportional random sampling from all the students of class VII. Data on menstrual patterns were obtained through structured questionnaires. Data were analyzed by Pearson's Product Moment correlation, Rank Spearman. Most subjects had 82.53% disminorhe symptoms. The results showed that there was effect of curcumin (r = 0.637; p = 0.000) with disminore symptoms. Combination of TTD with curcumin 10 mg can reduce disminore equal to (64.7%) with p value <0.001.